Prostatic Artery Embolization is Similarly Efficacious to Transurethral Resection of the Prostate (TURP) with a Better Safety Outcome: A Systematic Review and Meta-Analysis - Maulida Shafi; Zumirda Zumirda (Eduvest - Journal of Universal Studies, 2026)
Benign prostatic hyperplasia (BPH) is a prevalent condition affecting over 50% of men aged 60 years and older, often leading to lower urinary tract symptoms (LUTS) that significantly reduce quality of life. Transurethral resection of the prostate (TURP) remains the standard treatment for moderate to severe BPH; however, it is associated with notable complications. Prostatic artery embolization (PAE) has emerged as a minimally invasive alternative with potential advantages in safety and recovery. This study aims to evaluate and compare the safety and efficacy of PAE and TURP in treating BPH, focusing on symptom improvement, prostate volume reduction, hospital stay duration, and adverse events. A systematic review and meta-analysis were conducted following PRISMA guidelines. Literature searches were performed in PubMed, the Cochrane Library, and ScienceDirect up to May 3, 2025. Studies comparing PAE and TURP reporting outcomes such as IPSS, prostate volume, length of stay, and adverse events were included. Data extraction and quality assessment were conducted using the RoB-2 tool, while statistical analysis was performed using Review Manager version 5.4. The findings revealed a non-significant trend favoring PAE in improving IPSS scores (mean difference -2.71, p=0.12) and reducing prostate volume (mean difference -9.62 mL, p=0.08). However, PAE significantly reduced hospital stay duration (mean difference -1.52 days, p<0.0001) and showed a lower risk of severe adverse events (relative risk 0.37, p=0.05) compared to TURP. In conclusion, PAE demonstrates comparable effectiveness to TURP with improved safety and shorter hospitalization, making it a promising minimally invasive alternative.